Colonic Basidiobolomycosis-An Unusual Presentation of Eosinophilic Intestinal Inflammation - Elena Kurteva; Alasdair Bamford; Kate Cross; Tom Watson; Catherine Owens; Fanlek Cheng; John Hartley; Kathryn Harris; Elizabeth M. Johnson; Keith Lindley; Samantha Levine; Jutta Köglmeier (Frontiers Media S.A., 2020)
Basidiobolomycosis is a rare fungal disease caused by Basidiobolus ranarum. Involvement of the gastrointestinal tract is unusual and poses both a diagnostic and therapeutic challenge, as clinical signs are non-specific and predisposing risk factors are lacking. It can mimick inflammatory bowel disease, primary immunodeficiency, or a malignancy and should be considered in patients who do not respond to standard therapy. We present the case of a 22 months old boy with confirmed colonic Basidiobolomycosis, who presented with severe eosinophilic inflammation of the gastrointestinal tract. Panfungal PCR performed on DNA extracted directly from a tissue sample confirmed the presence of Basidiobolus. He made a full recovery with a combination of surgery and prolonged targeted antifungal medication.